PENGARUH PEMADANAN NIK MENJADI NPWP TERHADAP PENGKINIAN DATA PELANGGAN DI PT. BORWITA CITRA PRIMA - Estevania Angel Gloria; Indrawati Yuhertiana (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
. This study examines the impact of integrating the National Identification Number (NIK) as the Taxpayer Identification Number (NPWP) on customer data at PT. Borwita Citra Prima. Tax is a mandatory contribution from the public to the state, vital for economic development and public welfare. However, there is a significant gap between the number of taxpayers and working individuals in East Java, attributed to complex tax regulations. The Indonesian government aims to improve tax compliance by implementing the Single Identity Number (SIN), where NIK serves as NPWP. This research uses a qualitative case study approach, involving interviews and observations with 5 informants from PT. Borwita Citra Prima's administration and sales departments. The findings reveal that using NIK as NPWP enhances tax compliance, administrative efficiency, and data accuracy, thereby supporting better business strategies and market analysis.